2022
DOI: 10.2147/jaa.s373307
|View full text |Cite
|
Sign up to set email alerts
|

Association of Allergic Sensitivity and Pollination in Allergic Respiratory Disease: The Role of Pollution

Abstract: Purpose To evaluate the association between allergic sensitivity and pollen counts in patients with allergic respiratory disease (ARD) and its relationship with atmospheric pollutants. Methods From 2012 to 2018, we evaluated the sensitivity by skin prick test in ARD patients. The pollen counts were analyzed according to international guidelines (2014–2018). The pollutant and meteorological data were obtained at the same time from AIRE-CDMX websites. We analyzed the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In this sense, a study carried out in Madrid city reported a positive correlation between Poaceae pollen loads and O 3 concentration outside the clinically relevant season [ 38 ]; other research carried out in Bratislava pointed to a strong and significant positive correlation between Poaceae airborne pollen and several air pollutants (PM 10 , PM 2.5 , CO, O 3 , and NO 2 ) [ 39 ], while the pollen allergenic potency was positively significantly correlated with NO 2 levels [ 40 ]. In Mexico City, it was observed that the amount of Fraxinus and Cupressaceae pollen was correlated with increases in NO 2 , PM 10 , and PM 2.5–10 [ 41 ]. NO 2 was shown to react with the pollen grains, inducing the degradation of its structure, which further leads to protein amount changes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, a study carried out in Madrid city reported a positive correlation between Poaceae pollen loads and O 3 concentration outside the clinically relevant season [ 38 ]; other research carried out in Bratislava pointed to a strong and significant positive correlation between Poaceae airborne pollen and several air pollutants (PM 10 , PM 2.5 , CO, O 3 , and NO 2 ) [ 39 ], while the pollen allergenic potency was positively significantly correlated with NO 2 levels [ 40 ]. In Mexico City, it was observed that the amount of Fraxinus and Cupressaceae pollen was correlated with increases in NO 2 , PM 10 , and PM 2.5–10 [ 41 ]. NO 2 was shown to react with the pollen grains, inducing the degradation of its structure, which further leads to protein amount changes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%